Pengaruh Inklusi Keuangan Digital, Literasi Keuangan Digital, dan Akses Permodalan terhadap Profitabilitas Usaha Mikro Di Kota Palu - Masriani; Sastrawan, Erwan; Rianty, Cici; Annisah (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of digital financial inclusion, digital financial literacy, and access to capital on micro-enterprise profitability in Palu City. Using a quantitative associative approach, data from 100 micro-enterprise respondents were analyzed through multiple linear regression. The results show that the three variables simultaneously affect profitability (R² = 0.641). Partially, digital financial inclusion has no significant effect, digital financial literacy has a positive significant effect, and access to capital has a negative significant effect. Digital financial literacy is the most dominant factor influencing micro-enterprise profitability in Palu City.